Sedimentary Processes Examples from Asia, Turkey and Nigeria - Aiello, Gemma (IntechOpen, 2020)
This book contains six chapters covering the sedimentary processes with examples from Asia, Turkey, and Nigeria. The book focuses on the geological characteristics, beach processes, coastal and lacustrine sedimentary archives, and the role of mangroves in controlling coastal sedimentation. In more detail, these topics are pertaining to the geological characteristics and the production response of a reservoir located offshore the Niger Delta (Nigeria), the coastal lacustrine geo-archives with the example of the Lake Bafa (Turkey), the sedimentary processes in the riparian zone of the Ruxi Tributary Channel (Three Gorges Reservoir, China), the beach morphological changes studied by means of a contour-line change model and finally, the role of the mangroves in controlling the sedimentary accretion of coastal and marine environments with the regional example of the south-eastern Asia.